2016
DOI: 10.1016/j.apenergy.2015.05.099
|View full text |Cite
|
Sign up to set email alerts
|

Steady state analysis of gas networks with distributed injection of alternative gas

Abstract: h i g h l i g h t sA steady-state analysis method for gas networks was developed. This method is used for gas networks with distributed injection of alternative gas. A gas network with injection of upgraded biogas and hydrogen was simulated. Results show the impact on pressure and gas quality in the network. a b s t r a c tA steady state analysis method was developed for gas networks with distributed injection of alternative gas. A low pressure gas network was used to validate the method. Case studies were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(82 citation statements)
references
References 9 publications
0
76
0
Order By: Relevance
“…Current research aims to refine this range of allowable injections. 280,[288][289][290][291] A Dutch study concluded that off-the shelf gas appliances operated with no serious problems with up to 20% hydrogen blends by volume. 292 Similarly, the Health and Safety Laboratory concluded that 20% hydrogen was unlikely to harm the UK gas network or most appliances, although the identification and modification of vulnerable appliances is required for concentrations above 10%.…”
Section: Hydrogen Distributionmentioning
confidence: 99%
“…Current research aims to refine this range of allowable injections. 280,[288][289][290][291] A Dutch study concluded that off-the shelf gas appliances operated with no serious problems with up to 20% hydrogen blends by volume. 292 Similarly, the Health and Safety Laboratory concluded that 20% hydrogen was unlikely to harm the UK gas network or most appliances, although the identification and modification of vulnerable appliances is required for concentrations above 10%.…”
Section: Hydrogen Distributionmentioning
confidence: 99%
“…Given the two variables of the pipeline flow, the pressure at the beginning of the pipeline, and the pressure at the end, the unknown variable can be solved. According to the conservation law of natural gas hydrodynamic mass and Bernoulli's equation, the natural gas flow equations of different pressure levels based on certain assumptions are as follows [19,20]:…”
Section: Natural Gas Pipeline Modelmentioning
confidence: 99%
“…Many authors for simplification neglect the inclination term; however, Matko, Kwabena, and Iterran-Gonzales [22][23][24][25] are some authors who have considered inclination in the pipe flow equation, because of its importance for the validation of models with real-world data. Simulation of a natural gas network focusing on gas quality using a numerical-iteration method was carried out by Abeysekera [26]. An important point of this literature is the inclusion of gases with different density in the network.…”
Section: Literature Reviewmentioning
confidence: 99%